STRATEGI MITIGASI BENCANA TANGGUL LAPINDO DI DESA GEMPOLSARI: DISASTER MITIGATION STRATEGY OF LAPINDO EMPIRE IN GEMPOLSARI VILLAGE - Shazana Dhiya Ayuni; Jamaaluddin; Sy. Syahrorini (Program Studi Teknologi Informasi, 2021)
The leakage of natural gas drilling carried out by PT. Lapindo Brantas, resulted in 3 sub-districts in Sidoarjo affected by mudflow. Since 2006 untill now per-January 2021, the embankments that’s have been built often collapsed, leakage or burst. Meanwhile, there has been no disaster mitigation action when it happened. So far, when the mud flows into residents’s houses, the authorities have taken a long time to act the disaster. And the residents anticipate themselves when the mud overflows their house. So it is necessary to have disaster mitigation strategy that also collaborates with others parties in sub-districts. So that rhe local residents know what to do when disaster happened. Disaster mitigation strategies that will be carried out include pre-disaster, during disaster and post-disaster. With that result residents have a sense of security even though they live in disaster-prone areas.